Exploring evidence for a prospective relationship between common mental disorder and meeting residential mobility preferences. (March 2015) - Woodhead, Charlotte; Aschan, Lisa; Lynskey, Michael T.; Polling, Catherine; Goodwin, Laura; Hatch, Stephani L.
Abstract: This study investigates evidence of a selective influence of mental health in meeting residential mobility preferences. Data from two waves of Understanding Society (the UK Household Longitudinal Study) were used to identify four preference-mobility groups ('desired stayers', 'entrapped', 'desired movers', 'displaced'). Associations between mental health (symptoms of common mental disorder, CMD) and preference-mobility groups were measured both before and after residential moves. Those identified with CMD at baseline were at greater risk of being both in the 'entrapped' and the 'desired mover' groups, relative to the 'desired stayer' group in the following year. The association between preference-mobility group and subsequent poorer mental health was found among both groups that failed to meet their mobility preferences ('entrapped' and 'displaced'). This study finds evidence for a selective influence of mental health - such that those with poorer mental health are less likely to achieve a desired residential move, and highlights the importance of considering a bidirectional relationship between residential mobility and mental health.